The architectural structure of the Kazakh people and its educational value - Baidabekov, Әуез; Malibekov , Жандарбек (Рroblems of engineering and professional education, 2023)
In the article, the manufacture of a yurt, its tailoring and assembly is a big deal that caused the problem, an explanatory note about its collection and demolition due to the lack of it now no one can sew or tear and the lack of explanation of its structure and practical training, as well as together into four main sections depending on the interior of the yurt and its use provided that it is divided. The article describes the general architectural structure of the yurt. The internal structure and educational value of the yurt are considered.